(untitled) (Journal of Pathology of Nepal, 2013)
Background: Xeroderma pigmentosum is a rare autosomal recessively inherited disorder affecting 1 in 2,50,000 population. It shows genetic heterogeneity with at least ten different complementation groups identified which have different clinical presentations. They tend to have a more than 1000 fold increased risk of developing cancers in sun-exposed areas as a result of a DNA repair defect. This study presents a myriad of histopathological features of malignancies seen in individuals with this rare. Materials and Methods: Biopsies received from patients with a clinical diagnosis of Xeroderma Pigemntosa at the department of pathology, Institute of Medicine, Tribhuvan University Teaching Hospital, Kathmandu, from April 2008 to June 2012 were included in the study. Hematoxylin and eosin stained sections were examined. Clinical history was retrieved from the computer data base of the department. Results: During the study period, a total of eleven cases of Xeroderma pigmentosum presented with a biopsied lesion. All of these were malignant lesions. No benign lesions were seen. The age range of these patients was 6-30years with a mean of 18.8 years. The male to female ratio was 4.5:1. The most common malignancy seen was squamous cell carcinoma 7/11 (63.6%) followed by basal cell carcinoma 2/11 (27.2%). A single case presented with basal cell carcinoma of face and melanoma of trunk. The frequently observed site of malignancy was skin of the face followed by conjunctiva. Conclusion: In our population, non melanotic skin cancers affecting the face are more common in young individuals with Xeroderma pigmentosum. DOI: http://dx.doi.org/10.3126/jpn.v3i6.8996 Journal of Pathology of Nepal (2013) Vol. 3, 472-475